EFEKTIFITAS VAKSINASI HUMAN PAPILLOMAVIRUS (HPV) DALAM MENCEGAH KEJADIAN KANKER SERVIKS (REVIEW LITERATUR - Maria Lupita Nena Meo (NHM PRESS, 2022)
Cervical cancer accounts for 8.8% of cancer deaths in Indonesia, making it the second leading cause of cancer deaths. The World Health Organization has recommended the human papillomavirus (HPV) vaccination as a preventive measure against cervical cancer. This review aims to provide an evidence-based summary of the effectiveness of HPV vaccination. Literature study on English-language articles collected from the online database PubMed, Google Scholars, and DOAJ with search keywords